NATURE+ in Colombia - Report 2023 & Outlook 2024 - Ortiz Escobar, Natalia; Ramírez, Marleni (2023)
In Colombia, NATURE+ works in the southwest departments of Caquetá, Cauca, Nariño, Putumayo and Valle del Cauca with a focus on two landscapes: lowlands and highlands. These areas have high deforestation rates, at-risk Indigenous populations and latent security risks. However, communities, governments and researchers have recognized the departments’ importance for water and agrobiodiversity conservation, and are beginning to embrace nature-positive activities to improve the natural environment and the lives of the people who depend on